The essential jewel of holy practice - Vjigs-med-chos-dbang 1808-1887; Garfield, Jay L. 1955-; McRae, Emily 1981- (Wisdom Publications, 2017)
"Patrul Rinpoche (1808-1887) was one of the most important Dzogchen teachers in nineteenth-century Tibet. His lineage comprises many of the greatest Dzogchen teachers of the twentieth century. The Essential Jewel is among his most beautiful compositions, although it may not be his best known. The poem synthesizes Madhyamaka philosophy and the Dzogchen perspective in a compelling admonition to engage in religious practice aimed at self-perfection. The Essential Jewel is an extraordinary poetic work. Patrul Rinpoche's voice is urgent, personal, compelling, and expressed for the most part in direct earthy language, although it is also replete with precise, technical terminology. The Essential Jewel is also philosophically profound. It draws on ideas grounded in Madhyamaka philosophy and Buddhist ethical theory as well as ideas and practices central to the Dzogchen tradition. Patrul Rinpoche's genius lies in part in his unique ability to articulate a precise philosophical vision in an accessible poetic voice and to do this in the context in an urgent admonition to practice. This translation aims to present this poem in a way that reflects Patrul Rinpoche's poetic voice with sufficient precision to convey his philosophical ideas. It provides an introduction that should give the reader a foundation to read the poem as well as explanatory notes at points where the poem contains references or terminology that may not be accessible to the Western reader"...
Includes bibliographical references and index
Keywords: RELIGION / Buddhism / Tibetan / bisacsh; RELIGION / Eastern / bisacsh; RELIGION / Ethics / bisacsh; Rdzogs-chen; RELIGION / Buddhism / Tibetan; RELIGION / Eastern; RELIGION / Ethics; Buddhistische Philosophie